Enhancing iron and zinc bioavailability in maize (Zea mays) through phytate reduction: the impact of fermentation alone and in combination with soaking and germination - Nsabimana, Samuel; Ismail, Tariq; Lazarte, Claudia E. (Frontiers in Nutrition, 2024)
Phytates are nutrient-binding compounds found mainly in cereals and legumes, which may significantly contribute to micronutrient malnutrition in regions where phytate-rich cereals, such as maize, are staple food. Objectives. This study investigated how maize fermentation, both alone and in combination with soaking and germination, can reduce phytate levels and enhance the estimated bioavailability of iron and zinc. Methods. We evaluated various fermentation methods, including spontaneous fermentation; fermentation with starter cultures, either Lactiplantibacillus plantarum 299v® (Lp299) or yogurt containing viable Lacticaseibacillus casei; and fermentation with Lp299 of soaked and germinated maize. The outcome variables included changes in pH and lactic acid content during fermentation, and measurements of phytate levels (spectrophotometry), minerals (Atomic absorption) and protein (protein analyzer) in maize samples before and after treatments. Results. Fermentation with Lp299 of soaked and germinated maize grains yielded a phytate reduction of up to 85.6% decreasing from 9.58±0.05 g•kg -1 in raw maize to 1.39±0.09 g•kg -1 after processing. Fermentation of raw maize flour using Lp299 or yogurt resulted in a similar phytate reduction of 65.3% (3.35±0.26 g•kg -1 ) and 68.7% (3.02±0.01 g•kg -1 ) respectively. Spontaneous fermentation yielded a phytate reduction of 51.8 % (4.65±0.40 g•kg -1 ). This reduction in phytate content enhanced the estimated bioavailability of iron and zinc, particularly in the soaking-germination-fermentation combination, where the Phytate:Zinc molar ratio (Phy:Zn) dropped from 40.76 to 7.77, representing 81% reduction from the raw maize. The Phytate:Iron molar ratio (Phy:Fe) dropped from 41.42 to 6.24 indicating an 85% reduction. Additionally, fermentation led to a significant increase (p=0.001) in protein content in maize flour after fermentation, ranging from 7.3% to 10.3% after the various fermentation treatments. There was not significant difference in the protein increase when compared the fermentation types. Conclusion. Lactic acid fermentation of soaked and germinated maize grains, emerged as the most promising process to enhance the bioavailability of essential minerals. This approach could help alleviate mineral deficiencies in populations dependent on maize-based diets. The findings underscore the potential of fermentation to be applied at the household level, bringing up an alternative for programs and policies focused on reducing micronutrient deficiencies.